Difficulties and facilities for notification of sexual partners with sexually transmitted infections - Elani Graça Ferreira Cavalcante; Ivana Cristina Vieira de Lima; Ana Karina Bezerra Pinheiro; Mahara Coelho Crisostomo Miranda; Marli Teresinha Gimeniz Galvão (Rev Rene)
Objective: to understand the difficulties and facilities of professionals to notify sexual partners with sexually transmitted infections. Methods: qualitative study carried out with 19 professionals from four referral services in sexually transmitted infections. A semistructured interview was conducted and the statements were analyzed through Content Analysis technique. Results: the difficulties identified were: diversity of types of sexual relationships, resistance of the index patient, emphasis on information transmission, ineffective verbal communication, insufficient time and absence of monitoring. The facilities were: respect for patient autonomy, counseling free of judgments, effective verbal communication, motivation and negotiation, written communication, confidential environment, partnership with the multiprofessional team, communication through card to evaluate effectiveness of notification.Conclusion: based on the competencies, communication was identified as a facilitator of empowerment of the index patient in the process of to reveal the infection to the contacts, and weaknesses emerged in the conduct of cases about the knowledge, planning, implementation, partnership and evaluation.